BENCHMARKING ANALYSIS FOR THE DEVELOPMENT STRATEGY OF UPJA CAHAYA BINTANG (AGRICULTURAL MACHINERY SERVICE UNIT) MUARA ENIM - Rabecha Maros Framita; Lainatussifa; Fitri Yunda Sari (AGRIBUSINESS JOURNAL, 2025)
A follow-up study is important to evaluate the competitiveness of UPJA Cahaya Bintang through benchmarking analysis against similar business units in other regions. The results show that UPJA Cahaya Bintang has a well-structured organization and diversified services; however, it still lags in terms of financial feasibility, utilization of digital technology, and partnership development. The benchmarking analysis reveals the need for strategies to strengthen institutional capacity, diversify services, enhance human resource competencies in technology application and digital outreach, and reinforce partnerships to improve the competitiveness of UPJA Cahaya Bintang. This study recommends organizational restructuring with a clear division between technical and administrative functions, implementation of digitalized operational processes and recording systems, innovation in the diversification of agricultural machinery rental services, capacity building for human resources, and strengthening partnerships with formal institutions.